Genomewide linkage scan reveals novel loci modifying age of onset of Huntington's disease in the Venezuelan HD kindreds. - Gayán, J; Brocklebank, D; Andresen, J; Alkorta-Aranburu, G; Zameel Cader, M; Roberts, SA; Cherny, S; Wexler, N; Cardon, L; Housman, D (2008)
The age of onset of Huntington's disease (HD) is inversely correlated with the CAG length in the HD gene. The CAG repeat length accounts for 70% of the variability in HD age of onset. However, 90% of individuals worldwide with expanded alleles possess between 40 and 50 CAG repeat lengths in their HD gene. For these people, the size of their repeat only determines 44% of the variability in their age of onset. Once the effect of the CAG repeat has been accounted for, the residual variance in age of onset is a heritable trait. Targeted candidate gene studies and a genome scan have suggested some loci as potential modifiers of the age of onset of HD. We analyzed the large Venezuelan kindreds in which the HD gene was originally identified. These kindreds offer greater analytic power than standard sib-pair designs. We developed novel pedigree-member selection procedures to maximize power. Using a 5,858-single-nucleotide-polymorphism marker panel, we performed a genomewide linkage analysis. We discovered two novel loci on chromosome 2. Chromosome 2p25 (logarithm of the odds ratio (LOD)=4.29) and 2q35 (LOD=3.39) may contain genes that modify age of onset. A third linkage peak on chromosome 6q22 (LOD=2.48) may confirm the most promising locus from a previous genome scan. Two other candidate loci are suggestive on chromosome 5 (LOD=3.31 at 5p14 and LOD=3.14 at 5q32). All these regions harbor candidate genes that are potential HD modifier genes. Finding these modifier genes can reveal accessible and promising new therapeutic pathways and targets to ameliorate and cure HD.